2020
DOI: 10.1186/s42834-020-00061-9
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Lead, manganese, and copper onto biochar in landfill leachate: implication of non-linear regression analysis

Abstract: The feasibility of using wood-derived biochar (BC) to remove Pb, Mn, and Cu from landfill leachate was investigated and modeled in this study. BC was produced under the pyrolytic temperature of 740 °C. The effect of contact time, BC dosage and particle size on adsorption of the heavy metals onto BC was examined. BC was used in two forms i.e., pulverized (PWB) and crushed (CWB) to evaluate the effect of BC particle size on adsorption characteristics. The kinetics of Pb, Mn, and Cu adsorption onto PWB and CWB we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 47 publications
2
32
0
Order By: Relevance
“…They found that the non-linear forms of the equations gave a better representation of the equilibrium isotherm for Cu where Fritz-Schlunder IV provided the best fit. The adsorption isotherms for Pb, Cu and Mn in a three solute system was best fitted with non-linear Freundlich equation as reported by Zand et al [50]. Based on the Freundlich isotherm for this research, the most adsorbed metals (Pb, Cd and Cu) occupied the exponentially distributed active sites most likely by virtue of their hydrated ionic radii and electronegative attraction to the binding sites [36,39,47,48].…”
Section: Zvk-fau Nonlinear Adsorption Isothermssupporting
confidence: 55%
“…They found that the non-linear forms of the equations gave a better representation of the equilibrium isotherm for Cu where Fritz-Schlunder IV provided the best fit. The adsorption isotherms for Pb, Cu and Mn in a three solute system was best fitted with non-linear Freundlich equation as reported by Zand et al [50]. Based on the Freundlich isotherm for this research, the most adsorbed metals (Pb, Cd and Cu) occupied the exponentially distributed active sites most likely by virtue of their hydrated ionic radii and electronegative attraction to the binding sites [36,39,47,48].…”
Section: Zvk-fau Nonlinear Adsorption Isothermssupporting
confidence: 55%
“…The Langmuir model is usually applied to describe homogeneous adsorption, considering that all adsorption sites on the surface of a biosorbent have equal solute affinity [ 35 ]. The maximum sorption capacity obtained by using the Langmuir isotherm for all systems was significantly higher than experimentally obtained values.…”
Section: Resultsmentioning
confidence: 99%
“…Removal of Pb by other active adsorbents has been studied in previous researches. Daryabeigi Zand and Rabiee Abyaneh [27] reported that the removal of Pb by a crushed wood-derived biochar (10 g L -1 ) after 1400 min was 60%. Ablouh et al [28] showed that the maximum adsorption of Pb from an aqueous solution by a green adsorbent based on chitosan microspheres/sodium alginate hybrid beads was 60 %.…”
Section: Resultsmentioning
confidence: 99%